Exploring the Borrowing Words in English Language Learning: A Case Study of Universitas Islam Riau Students - Rugaiyah, Rugaiyah; Ariyanto, Joko (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This research aims to assess the understanding of English-borrowing words among fifth-semester students at Universitas Islam Riau, Pekanbaru. The methodology employed involved a test consisting of 30 questions, categorized into three types: 10 questions each for loanwords, blend words, and loan shifts. A total of 50 students from the fifth semester of English language in the academic year 2023/2024 participated in the study, providing insights into their vocabulary comprehension. The findings revealed that the term "active" achieved the highest percentage of correct answers at 90%, indicating strong familiarity among students. Conversely, the term "terror" recorded the lowest recognition rate at 64%, suggesting challenges in understanding its complex connotations. Other terms, including "program" (80%) and "application," "technique," "quality," and "information" (76%), demonstrated moderate performance levels, highlighting gaps in comprehension that warrant further attention. The novelty of this research lies in its focused examination of various types of loan-blended words and their specific performance levels among Indonesian learners. This study not only contributes to the existing literature on vocabulary acquisition but also emphasizes the importance of targeted instructional strategies to enhance students' proficiency in recognizing and using loan-blended words effectively. By addressing identified gaps through engaging teaching methods, educators can facilitate improved vocabulary acquisition and overall language skills among students, thereby enriching their educational experience in an increasingly globalized linguistic landscape